PENGARUH PENGGUNAAN MEDIA PENDIDIKAN OLEH GURU BK TERHADAP MOTIVASI PESERTA DIDIK DALAM MENGIKUTI LAYANAN INFORMASI (Studi di Kelas VIII SMP Negeri 20 Padang) - Rona, Afri - (Bimbingan dan Konseling, 2014)
This research is motivated by the existence of the phenomenon at the time of provision of information services like ongoing learners permit out, talking with friends, walk in the classroom, teasing, playing mobile phones and the lack of interaction and feedback provided learners when information service delivery. The researchers raised concerns about how research influences educational media use by teachers BK on the motivation of learners in the following information services (studies in class VIII SMP 20 Padang). This type of research is descriptive quantitative method. The study population was a class VIII students of SMP Negeri 20 Padang. Sampling using simple random sampling technique which amounts to 68 respondents. The instrument used was a questionnaire. Analysis of data using simple linear regression formula to look at the effect of the use of educational media by BK teacher to learner motivation in following information services (studies in class VIII SMP 20 Padang). Results of the study: (1) description of the use of educational media to be in the good category with the percentage of 85.29%. (2) description of the motivation of learners at the high category with a percentage of 76.4%. (3) The effect of the use of educational media obtained thitung 4.180> and ttable of 0.23 with significance level of 0.000 (sig <0.05). So the results, the effect of the use of educational media to motivate learners in the following service information on Junior High School eighth grade 20 Padang with enough relationship level. The results of this study can be recommended to BK teachers to keep using the media to make the students stay motivated to follow the service information.